2014
DOI: 10.1016/j.pbb.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Guanosine prevents behavioral alterations in the forced swimming test and hippocampal oxidative damage induced by acute restraint stress

Abstract: Guanosine is a guanine-based purine that modulates glutamate uptake and exerts neurotrophic and neuroprotective effects. In a previous study, our group demonstrated that this endogenous nucleoside displays antidepressant-like properties in a predictive animal model. Based on the role of oxidative stress in modulating depressive disorders as well as on the association between the neuroprotective and antioxidant properties of guanosine, here we investigated if its antidepressant-like effect is accompanied by a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 79 publications
3
38
0
Order By: Relevance
“…This antioxidant activity may be related, at least partially, to its ability to stimulate the endogenous antioxidant response. This hypothesis is in agreement with previous studies showing that this nucleoside can induce an increase in the expression and/or activity of endogenous antioxidant enzymes such as HO-1 [92,100] and superoxide dismutase (SOD) [97].…”
Section: Protective Effects Of Guanosine In Neurodegenerative Diseasessupporting
confidence: 93%
See 2 more Smart Citations
“…This antioxidant activity may be related, at least partially, to its ability to stimulate the endogenous antioxidant response. This hypothesis is in agreement with previous studies showing that this nucleoside can induce an increase in the expression and/or activity of endogenous antioxidant enzymes such as HO-1 [92,100] and superoxide dismutase (SOD) [97].…”
Section: Protective Effects Of Guanosine In Neurodegenerative Diseasessupporting
confidence: 93%
“…In addition, we also demonstrated that this behavioral effect of guanosine appears to be dependent, at least in part, on the antioxidant properties of this nucleoside, since the guanosine-induced amelioration of the depressive-like behavior was accompanied by a reduction in oxidative stress through the restoration of the normal activity of endogenous antioxidant enzymes in the hippocampus. In particular, guanosine caused a significant increase in the activity of superoxide dismutase (SOD) in mice submitted to ARS, reinforcing the notion that some of the protective effects of this nucleoside are only observed following an initial insult [97]. Recently, we also found that chronic treatment (21 days) with guanosine has an antidepressant-like effect in the TST, which is likely unrelated to its acute effect, since in this study animals were tested 24 h after receiving the last guanosine dose.…”
Section: Protective Effects Of Guanosine In Mood Disorderssupporting
confidence: 52%
See 1 more Smart Citation
“…As a result of immobilization, the incidence of some neurochemical alterations in the brain can lead to neurobehavioral deficits such as immobility in the FST and TST (Wang, et al, 2016; Xu et al, 2017). The latter behavioral tests are widely employed to screen the efficiency of antidepressant drugs (Bettio et al, 2014; Cryan et al, 2005; Porsolt, et al, 1977). In agreement with other reports (Bettio, et al, 2014; Freitas et al, 2014), five days of sub-chronic restraint stress in our study resulted in an increase in the immobility time as compared to the control animals.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding these parameters, the decreased GPx and GR activities were found in the hippocampus of rats submitted to the chronic restraint stress procedure, a response that is probably related to an increase in the ROS production following the chronic stressor or decrease in the antioxidant production [35]. The overproduction of superoxide anion (O2•−) is one of the main factors involved in the stress-induced oxidative damage in the brain [36]. The present study has been indicated that the hippocampal activity of SOD was decreased in the rats submitted to chronic restraint stress.…”
Section: Discussionmentioning
confidence: 99%